Pengukuran Struktur Dan Kinerja Organisasi Industri: Aplikasi Pada Sektor Otomotif Indonesia - Mohtar Rasyid . (Universitas Kristen Maranatha, 2011)
Indonesian automotive industry recorded some progress as indicated by its growth. During peroid of 1999-2006, this sector experienced 8 percent growth rate on average. Production of automotive in 2005 reached 533.910 units motor vehicles and 5.074.204 motor cycles. Although the production volume in Indonesia is still much smaller than in order ASEAN countries like Thailand and Malaysia, the fact that Indonesia lies in emerging market with domestic rapidly expanding implies that there is still an opportunity for developing the industry. This paper explore development literature that related to structur, conduct and performance and investigate recent trend of the automotive industry performance. Beside of this, this paper examine influence of the market share, capital intensity, import intensity and labor productivity on automotive industry performance. Price-cost margin indicator is applied in measuring this performance. Base on the International Standard Industrial Classification (ISIC) 34100 (motor vehicles); 34200 (motor vehicles bodies); 34300 (component of motor vehicles), 35911 (motor cycles); 35912 (motorcycles component), the result shows that automotive industry performance in Indonesia relatively low (i.e. PCM above 50 percent on average).Keywords: industry performance, price-cost margin, automotive industry.